FOXO1 inhibition synergizes with FGF21 to normalize glucose control in diabetic mice - Yun-Kyoung Lee; Bryan Diaz; Marianne Deroose; Samuel X. Lee; Sandro Belvedere; Domenico Accili; Rudolph L. Leibel; Hua V. Lin (Elsevier, 2021)
Objective: Forkhead box protein O1 (FOXO1) plays a key role in regulating hepatic glucose production, but investigations of FOXO1 inhibition as a potential therapeutic approach have been hampered by a lack of selective chemical inhibitors. By profiling structurally diverse FOXO1 inhibitors, the current study validates FOXO1 as a viable target for the treatment of diabetes. Methods: Using reporter gene assays, hepatocyte gene expression studies, and in vivo studies in mice, we profiled our leading tool compound 10 and a previously characterized FOXO1 inhibitor, AS1842856 (AS). Results: We show that AS has significant FOXO1-independent effects, as demonstrated by testing in FOXO1-deficient cell lines and animals, while compound 10 is highly selective for FOXO1 both in vitro and in vivo and fails to elicit any effect in genetic models of FOXO1 ablation. Chronic administration of compound 10 improved insulin sensitivity and glucose control in db/db mice without causing weight gain. Furthermore, chronic compound 10 treatment combined with FGF21 led to synergistic glucose lowering in lean, streptozotocin-induced diabetic mice. Conclusions: We show that the widely used AS compound has substantial off-target activities and that compound 10 is a superior tool molecule for the investigation of FOXO1 function. In addition, we provide preclinical evidence that selective FOXO1 inhibition has potential therapeutic benefits for diabetes as a monotherapy or in combination with FGF21.